Effects of winter nutrition levels on cow and calf performance - R.R. Schalles; G. Kiracofe; C.L. Drake; C.N. Reves (Kansas Agricultural Experiment Station Research Reports, 1970)
Cow and calf performance under four winter-nutrition levels was compared using 34 cows the first year and 87 cows the second year. Cows were maintained on the same nutrition treatment both years with additional cows added the second year, Cows ranged from less than 2 to 11 years of age. Average calving date was early April. A total of 95 calves were included during the two years. Calves were weighed within 24 hours after birth and at monthly intervals from June to November. Cows were weighed each month. All cows were graded and calves were weaned and graded at the November weighing.
Keywords: Cattlemen' s Day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station); 536; Beef; Winter nutrition; Cow-calf performance